The Contributions of HIF-Target Genes to Tumor Growth in RCC - Zhang, Ting; Niu, Xiaohua; Liao, Lili; Cho, Eun-Ah; Yang, Haifeng (PloS one, 2013)
Somatic mutations or loss of expression of tumor suppressor VHL happen in the vast majority of clear cell Renal Cell Carcinoma, and it's causal for kidney cancer development. Without VHL, constitutively active transcription factor HIF is strongly oncogenic and is essential for tumor growth. However, the contribution of individual HIF-responsive genes to tumor growth is not well understood. In this study we examined the contribution of important HIF-responsive genes such as VEGF, CCND1, ANGPTL4, EGLN3, ENO2, GLUT1 and IGFBP3 to tumor growth in a xenograft model using immune-compromised nude mice. We found that the suppression of VEGF or CCND1 impaired tumor growth, suggesting that they are tumor-promoting genes. We further discovered that the lack of ANGPTL4, EGLN3 or ENO2 expression did not change tumor growth. Surprisingly, depletion of GLUT1 or IGFBP3 significantly increased tumor growth, suggesting that they have tumor-inhibitory functions. Depletion of IGFBP3 did not lead to obvious activation of IGFIR. Unexpectedly, the depletion of IGFIR protein led to significant increase of IGFBP3 at both the protein and mRNA levels. Concomitantly, the tumor growth was greatly impaired, suggesting that IGFBP3 might suppress tumor growth in an IGFIR-independent manner. In summary, although the overall transcriptional activity of HIF is strongly tumor-promoting, the expression of each individual HIF-responsive gene could either enhance, reduce or do nothing to the kidney cancer tumor growth.